The Employee Contributions to PFMA Non-Compliance Challenges in South Africa: Contributions From Limpopo Provincial Administration - Jonas MAKGOBA; Monde FAKU; Kabelo MOETI (PT Keberlanjutan Strategis Indonesia, 2025)
Compliance with the Public Finance Management Act is essential for the whole South African government. Nevertheless, the South African Auditor General has found non-compliance since most ministries within the provincial administration of Limpopo still violate the PFMA. Some of the non-compliance may lead to serious misstatements and, eventually, an AGSA qualified audit opinion. Noncompliance has a negative impact on the general population since it can occasionally lead to compromises in the quality of services provided by government bodies. The study assessed how personnel in departments of the province of Limpopo contributed to PFMA non-compliance. The study used an interview guide to gather the primary data and adhered to the qualitative research methodology. Purposive sampling was used to choose study participants based on their expertise with PFMA compliance across the province of Limpopo's various departments. Future PFMA compliance may be enhanced by the practical recommendations and ideas that the study generated. The study's consequences included identifying the problems that impact compliance in the public sector and providing recommendations for how to resolve them. Other aspects of the South African government are also impacted by the study's conclusions, such as the enhancement of PFMA compliance in the Limpopo public service administration.